Pengaruh Varian Produk Dan Promosi Online Terhadap Minat Beli Pada Keputusan Pembelian - prameswari, monica indah; Andayani, sri; Ida Pratiwi, Ni Made (Research Journal of Social Science and Economics, 2025)
This study aims to analyze and find out how much influence Product Variants and Online Promotion have on Purchase Decisions at Deliwafa Store Sidoarjo. The sampling technique uses purposive sampling, namely samples taken based on certain criteria. The sample used in this study was 100 samples, then the data obtained was analyzed using multiple regression analysis, this analysis includes: Validity Test, Reliability Test, Classical Assumption Test, Hypothesis Test through t test and F test, and analysis of the Coefficient of Determination (R). The results of the analysis using the t test can be seen that the two independent variables, namely Product Variance (X1) and Online Promotion (X2) partially have a significant effect on the dependent variable, namely Purchase Decision (Y) at the Deliwafa Store, Sidoarjo Branch. then the results of the analysis using the F test can be seen that the two independent variables, namely Product Variance (X1) and Online Promotion (X2) partially have a significant effect on the dependent variable, namely Purchase Decision (Y) at the Deliwafa Store, Sidoarjo Branch. The results of the analysis using the termination coefficient (R square) Product Variant (X1) and Online Promotion (X2) affect the Purchase Decision variable (Y).